Race, White Settler Liberalism, and the Nova Scotia Archives, 1931-1976 - McKay, Ian (Acadiensis, 2020)
This article explores the ways in which the Nova Scotia Archives confronted questions of race from 1934 to 1976. White settler colonialism provides a key to much of the archival work and historical reflection of such archivist-historians as D.C. Harvey and J.S. Martell. That outlook was preserved after 1945 by a new cohort of archivists, represented by C.B. Fergusson and Phyllis Blakeley. By the late 1960s, partly because of New Left ideas, apologies for empire ceded place to critical examinations of race and colonialism, as suggested by the pioneering works of Robin Winks and James St. G. Walker.